Haloperidol-induced painless legs and moving toe syndrome in a schizophrenia patient: a case report - Mugundan U Maheshwari; Natarajan Shanmugasundaram; Karthik Sankar; Mahendran Sekar; Ling S Wong; Sarvesh Sabarathinam; M Yasmin Begum; Srikanth Jeyabalan (Future Science OA)
Painless legs and moving toe syndrome (PoLMT) is a rare syndrome characterized by involuntary movements of the toe without pain. The exact etiology of the patient's PoLMT is unknown. We present a case of PoLMT in 45-year-old woman with a history of haloperidol intake for 10 months. Haloperidol was discontinued, and aripiprazole (15 mg) was initiated. After this switch, a reduction in movement was observed in the third and fourth toes; however, the second toe showed no discernible change.